Left Apical Aneurysm in a Patient with Severe Aortic Valve Stenosis - Drews, Thorsten; Pasic, Miralem; Hetzer, Roland (The Thoracic and Cardiovascular Surgeon Reports, 2014)
We report on a very rare case of left ventricular aneurysm in a 77-year-old patient with aortic valve stenosis and without coronary artery disease. The patient underwent conventional aortic valve replacement and left ventricular aneurysmectomy with an uneventful postoperative course. The cause of the left ventricular aneurysm was suspected to be a long history of aortic valve stenosis that led to severe intraventricular hypertension, subsequently asymmetric septum hypertrophy, and finally apical aneurysm.
Keywords: aneurysm; heart diseases; hypertension; valves